TM4SF5-Mediated Roles in the Development of Fibrotic Phenotypes - Jihye Ryu; Jung Weon Lee (Hindawi Limited, 2017)
Transmembrane 4 L six family member 5 (TM4SF5) can form tetraspanin-enriched microdomains (TERMs) on the cell's surface. TERMs contain protein-protein complexes comprised of tetraspanins, growth factor receptors, and integrins. These complexes regulate communication between extracellular and intracellular spaces to control diverse cellular functions. TM4SF5 influences the epithelial-mesenchymal transition (EMT), aberrant multilayer cellular growth, drug resistance, enhanced migration and invasion, circulation through the bloodstream, tumor-initiation property, metastasis, and muscle development in zebrafish. Here, current data on TM4SF5's roles in the development of fibrotic phenotypes are reviewed. TM4SF5 is induced by transforming growth factor β1 (TGFβ1) signaling via a collaboration with epidermal growth factor receptor (EGFR) activation. TM4SF5, by itself or in concert with other receptors, transduces signals intracellularly. In hepatocytes, TM4SF5 expression regulates cell cycle progression, migration, and expression of extracellular matrix components. In CCl4-treated mice, TM4SF5, α-smooth muscle actin (α-SMA), and collagen I expression are observed together along the fibrotic septa regions of the liver. These fibrotic phenotypes are diminished by anti-TM4SF5 reagents, such as a specific small compound [TSAHC, 4'-(p-toluenesulfonylamido)-4-hydroxychalcone] or a chimeric antibody. This review discusses the antifibrotic strategies that target TM4SF5 and its associated protein networks that regulate the intracellular signaling necessary for fibrotic functions of hepatocytes.